Congenital extraskeletal Ewing's sarcoma of chest wall - A rare case report - Bhagyalakshmi Atla; B Satya Vara Prasad; K Satya Sri; Geeta Vandana (Wolters Kluwer Medknow Publications, 2011)
Congenital extraskeletal Ewing's sarcoma or peripheral primitive neuroectodermal tumor is an extremely uncommon and invariably fatal tumor. We report a case of extraskeletal congenital Ewing's sarcoma in a female fetus delivered at 34 weeks of gestation who died immediately after birth. In English literature, majority of cases of Ewing's sarcoma in neonates reported were skeletal. To the best of our knowledge, very few cases of extra-skeletal Ewing's sarcoma in neonates are reported in the literature.